Tough and Leniency of the Existence of Hindu Alukta in Tana Toraja South Sulawesi Indonesia - Segara, Nyoman Yoga; Putrawan, Nyoman Alit; Gunarta, Ketut; Brahman, Made Adi (International Journal of Psychosocial Rehabilitation, 2020)
This article is the result of the development of research on the history, existence, activities, and dynamics of the Alukta Hindus in Tana Toraja, South Sulawesi. The key issue to be explained is that although the Hindu Alukta followers have integrated with Hinduism, they still get the stigma and stereotype as animism and not religion. Structurally, they do not get the most attention from the government to be fostered through functional staff, such as instructors and teachers, while culturally, their knowledge of Hinduism also does not get the maximum understanding so that it is dominated by the implementation of local customs only. Based on this problem, theoretically, it is necessary to study the authority of the state which seems to have the authority to define local beliefs and official religion. In practice, this problem also has implications for regulations that should be comprehensive by providing guidance and services not only to “local religion” but also a community that chooses official religion as a “new religion”.